Evaluation of the relationship between the degenerative changes and bone quality of mandibular condyle and articular eminence in temporomandibular disorders by cone beam computed tomography - NAMDAR PEKİNER, FİLİZ MEDİHA (TAYLOR & FRANCIS LTD, 2022)
Objective: To evaluate whether there was a relationship between the degenerative bone changes and bone quality of the mandibular condyle and articular eminence in patients with temporomandibular disorder (TMD). Methods: The study group consisted of 100 patients with TMD. Diagnostic Criteria/TMD was used to identify the pathologies. Degenerative bone changes and bone qualities were detected by cone beam computed tomography; the bone qualities were classified using the Bone Quality Index (BQI) scale. Results: No statistically significant difference was found between degenerative bone changes and bone quality of the temporomandibular joint (TMJ) according to gender (p > 0.05). However, degenerative bone changes were more frequent than articular eminence in the mandibular condyle. BQI Type III was the most common bone quality among all types of degenerative bone changes. Discussion: Although no causality relationship was found between the bone quality and degenerative bone changes, low bone quality was found in TMD patients.
Keywords: Cone beam computed tomography; degenerative bone change; temporomandibular disorders; TMJ; OSSEOUS ABNORMALITIES; DIAGNOSTIC-CRITERIA; TMJ OSTEOARTHRITIS; JOINT DISEASE; RDC/TMD; PREVALENCE; AGE; RELIABILITY; OSTEOPHYTES